2016
DOI: 10.1161/hypertensionaha.116.06599
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Ouabain

Abstract: In this brief article, we summarize recent reports about endogenous ouabain (EO), a cardiotonic steroid (CTS). This includes analysis of mammalian EO, the discovery of EO isomers, regulation of intracellular signaling by EO, and the roles of EO in hypertension, pregnancy, and heart and kidney diseases. Novel ouabain-resistant mice that elucidate the key roles of α2 Na+ pumps and their CTS binding site are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 101 publications
0
49
0
1
Order By: Relevance
“…[30][31][32] After performing experiments with nifedipine, ouabain was incubated in an organ bath to investigate the possible role of Na + / K + ATP-ase in smooth muscle calcium ion trafficking related to serotonin action. Ouabain is an endogenous cardiotonic steroid hormone produced in the adrenal cortex, 33 and it is believed to be involved in salt sensitivity and hypertension. 34 By blocking the N + /K + ATP-ase at the level of smooth muscle cells, an increase in intracellular calcium will occur, and the contraction of the smooth muscle will be possible.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] After performing experiments with nifedipine, ouabain was incubated in an organ bath to investigate the possible role of Na + / K + ATP-ase in smooth muscle calcium ion trafficking related to serotonin action. Ouabain is an endogenous cardiotonic steroid hormone produced in the adrenal cortex, 33 and it is believed to be involved in salt sensitivity and hypertension. 34 By blocking the N + /K + ATP-ase at the level of smooth muscle cells, an increase in intracellular calcium will occur, and the contraction of the smooth muscle will be possible.…”
Section: Discussionmentioning
confidence: 99%
“…Other diseases such as renal failure [118], preeclampsia [119], myocardial ischemia/infarction [120,121], and diabetes mellitus [122,123] were also observed in association with elevated levels of endogenous compounds in human plasma samples. However, the accurate measurement of endogenous digitalis compounds in human samples still faces big challenges [124]. …”
Section: Na/k-atpase As a Novel Target For Cardiac Fibrosismentioning
confidence: 99%
“…A CTS was isolated from human plasma and was identified by mass spectrometry (MS) as endogenous ouabain (EO) or a ouabain isomer Mathews et al 1991). Nuclear magnetic resonance (NMR) and MS studies on human, bovine and rodent plasma and tissues verified that the endogenous substance is ouabain (Schneider et al 1998;Kawamura et al 1999;Komiyama et al 2000;Tashko et al 2010;Jacobs et al 2012;Hamlyn et al 2014); reviewed in Hamlyn & Blaustein, 2016). Moreover, recent studies identified two novel EO isomers that are not seen in commercial (plant) ouabain (Jacobs et al 2012;Hamlyn et al 2014).…”
Section: Introductionmentioning
confidence: 99%